COACHING SUPPORT (LAYANAN MATERNAL) MELALUI WAG KOLABORASI DENGAN BIDAN POLINDES BAGI IBU HAMIL DAN NIFAS - Indah Lestari; Noer Saudah; Catur Prasastia Lukita Dewi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Efforts to reduce maternal mortality through the provision of quality services must still be carried out despite the limited conditions due to the COVID-19 pandemic. Problems in pregnant women, childbirth and postpartum must be monitored even though ANC visits are limited. The purpose of this community service activity is to form a WhatsApp group as a medium to facilitate collaborative maternal services with the Punggul-Mojokerto Village Polindes Midwife and increase knowledge of reproductive mothers. The implementation of this activity will be carried out in September 2021, starting with the preparation stage to the evaluation stage. The outputs of this activity are the formation of WAG, consultation and mentoring activities for high risk pregnant women, preventive and promotive efforts in order to improve maternal and child health, available modules and booklets related to pregnancy, childbirth and postpartum, as well as increasing knowledge of reproductive mothers on maternal problems.